The relationship between mental well-being and stress in adolescents. - Heng, Zaneta En Hua. (2011)
This study examined the relationship between mental well-being and stress. Study 1 (Time1), examined the level of mental well-being and stress before intervention, using the Asian Mental Well-being Scale (AMWES) and the School Stress Scale. Participants were female primary school students (N= 65, mean age = 11.5). The participants went through intervention. Study 2 (Time 2) was conducted after the participants entered secondary school (N= 16, mean age =12.5). The AMWES showed high internal and test-retest reliability, and significant negative correlation with the stress measure. The stress intervention program significantly reduced school stress. Cross-lagged panel correlation analysis conducted on the results of Time 1 and Time 2 suggested a potential causal relationship between mental well-being and stress.